2014
DOI: 10.1063/1.4866604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spin induced magnetization on Jeans instability of viscous and resistive quantum plasma

Abstract: The effect of spin induced magnetization and electrical resistivity incorporating the viscosity of the medium is examined on the Jeans instability of quantum magnetoplasma. Formulation of the system is done by using the quantum magnetohydrodynamic model. The analysis of the problem is carried out by normal mode analysis theory. The general dispersion relation is derived from set of perturbed equations to analyse the growth rate and condition of self-gravitational Jeans instability. To discuss the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…[3][4][5][6] Goodman et al 7 have examined that the self-gravity plays a crucial role in the final stage of the star formation where dense cores (with size approximate 0.1 pc) inside molecular clouds collapse to form star-plus-disk system. The self-gravitation plays dominant role in many astrophysical systems viz., diffuse hydrogen clouds, diffuse molecular cloud and giant molecular clouds whose Jeans masses are, respectively, 795.13, 82.63, and 206.58 times of the solar mass.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Goodman et al 7 have examined that the self-gravity plays a crucial role in the final stage of the star formation where dense cores (with size approximate 0.1 pc) inside molecular clouds collapse to form star-plus-disk system. The self-gravitation plays dominant role in many astrophysical systems viz., diffuse hydrogen clouds, diffuse molecular cloud and giant molecular clouds whose Jeans masses are, respectively, 795.13, 82.63, and 206.58 times of the solar mass.…”
Section: Introductionmentioning
confidence: 99%
“…[5] By employing quantum theory, the study of charge particles and plasmas has gained much attention in astrophysical environments (e.g. The effect of spin induced magnetization, viscosity, and finite resistivity on the Jeans instability of quantum magneto plasma have been studied by Sharma and Chhajlani [10] using the quantum magnetohydrodynamic model. [3] Cheng and Wu [6] derived the basic equations for spin-1/2 quantum electron plasmas by considering spin-orbit coupling effect.…”
Section: Introductionmentioning
confidence: 99%
“…They have found that the right hand circularly polarized wave with spin-effects exists for larger k-values as compared to the spinless case, before it damps completely when comparing cold and hot plasma regimes. The effect of spin induced magnetization, viscosity, and finite resistivity on the Jeans instability of quantum magneto plasma have been studied by Sharma and Chhajlani [10] using the quantum magnetohydrodynamic model. Shahid et al [11] investigated the parallel propagating EM waves in electron-positron plasma using non-relativistic spin quantum fluid theory, where it is shown that, Faraday rotation appears with the inclusion of spin effect of plasma species which is absent in usual electron-positron plasmas without spin effects.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma & Chhajlani (2013) studied the influence of finite Larmor radius (FLR) effects on the Jeans instability of an infinitely conducting homogeneous quantum plasma using a quantum magnetohydrodynamic (QMHD) model. The effect of spin-induced magnetization and electrical resistivity on the Jeans instability of a viscous quantum plasma was also examined by Sharma & Chhajlani (2014). Prajapati & Chhajlani (2014) discussed the effects of quantum corrections on the Jeans instability of self-gravitating viscoelastic quantum fluids.…”
Section: Introductionmentioning
confidence: 99%